FITNESS LEVEL OF SECONDARY SCHOOL STUDENTS ENGAGED IN SPORTS - Danylevych, Myroslava; Romanchuk, Olha; Musikevych, Taras; Yurko, Nadiya; Stefanyshyn, Markiian (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
School physical education is effective means of providing children with the knowledge for lifelong physical activity. The research was aimed to examine the influence of different sports activities (badminton, basketball, football) on fitness level of boys aged 10-11. 72 boys aged 10-11 were engaged in the research. Evaluation of children’s fitness level involved anthropometric parameters of body length (cm); body mass (kg); hand dynamometry (kg). Cardiovascular and respiratory systems were also assessed: heart rate (HR, bpm) – method of palpation; blood pressure – systolic (SBP, mm Hg) and diastolic (DBP, mm Hg) – method of Korotkoff sounds; vital capacity of lungs (VC, L) – spirometer measuring. The Ruffier index, life index, strength index, the Robinson index and the Quetelet index were considered as well. Summing the points of five parameters, fitness levels were defined as low, below average, average, above average, and high. Comparative analysis of ball games influence on children’s fitness level revealed the highest growth rate among badminton players, though their initial and final parameters were the lowest ones. Research findings made it possible to conclude that extramural engagement in ball games throughout school year had beneficial effect on fitness levels of boys aged 10-11.